Physics Learning Outcomes With The Discovery Learning Model In Terms Of Class XI Student Motivation - Nurul Isnawati; Ahmad Harjono; I Wayan Gunada (Prodi Fisika FKIP Unram, 2020)
This study aims to determine the effect of siscovery learning model on learning outcomes in terms of learning motivation of class XI students in SMA Negeri 1 Batukliang. The study used was a quasi-experimental design with factorial 2x2. The population of this study was all students of class XI MIPA in SMA Negeri 1 Batukliang in academic year 2019/2020. Sampling using a cluster random sampling technique, obtained class XI MIPA 3 as a class experiment and class XI MIPA 2 as a control class. The study applies discovery learning in the experimental class and conventional learning in the control class. Data questionnaire to deteemine student obtained an average 74.00 and an average value of the control class of 54.74. Based on the result of data analysis it can be concluded that: 1) there is the effect of the siscovery learning model on the learning outcomes of students; 2) there is the effect of discovery learning models on students learning motivation; and 3) there is no intraction between discovery learning models and learning motivation towards students physics learning outcomes.